Green leaves, dry leaves, stalk fiber and the clarification of sugarcane juice (Scientia Agricola, 2001)
The presence of vegetal impurities in sugarcane delivered to sugarmills as green and dry leaves is a problem not only because they are non-value materials to be processed along with sugarcane stalks, but also because they can rise the color of the clarified juice and, consequently, the color of the sugar produced, with a reduction of its quality for the market. Another problem is the mud volume sedimented in the clarifiers, which also can result in a larger recirculation and greater volume of filtrate juice, with higher losses of sucrose and utilization of the vacuum rotary filters. The objective of this work was to observe the effect of the presence of green and dry leaves on sugarcane juice clarification, related to a control treatment with the addition of fiber extracted from the stalks. The experiments were planned based on the addition of quantities of fibrous sources in order to formulate samples with absolute increase of 0.25 , 0.50 and 0.75 percentual points over the fiber content of the sugarcane stalks (control treatment). The juice clarification was conducted with a laboratory clarifier. The clarified juice color and the mud volume were evaluated. The presence of green leaves caused higher color and mud volume due to the extraction of non-sucrose components of the leaves. Soluble compounds of dry leaves were also extracted, though not detected by juice analysis. The addition of the fiber extracted from the stalks did not induce alterations in the clarification process.